MiR-3196 acts as a Tumor Suppressor and Predicts Survival Outcomes in Patients With Gastric Cancer. (15th May 2020) - Chen, Guo; Wan, Jinliang; Wang, Zhenbo; Li, Lei; Jia, Hongying; Xing, Shaozhi; Chen, Shaoshui; Fan, Xiaocheng; Li, Rui
Background: Gastric cancer is one of the most common malignancies worldwide with high mortality. Therefore, identifying cancer-related biomarkers for predicting prognosis and progression of gastric cancer is essential. This study aimed to investigate the clinical value and functional role of microRNA-3196 in gastric cancer. Methods: The relative expression levels of microRNA-3196 in gastric cancer tissues and adjacent normal tissues were detected by quantitative reverse transcription-polymerase chain reaction. In this study, quantitative reverse transcription-polymerase chain reaction, cell proliferation assay, and Transwell migration and invasion assays were performed to explore microRNA-3196 expression level and its effects on cell proliferation, migration, and invasion in gastric cancer cells. The Kaplan-Meier method and multivariate Cox regression analyses were used to explore the prognostic significance of microRNA-3196 in gastric cancer. Dual-luciferase report assay was performed to validate the potential target gene regulated by microRNA-3196 in gastric cancer. Results: The expression of microRNA-3196 was downregulated in gastric cancer tissues and cell lines. Downregulation of microRNA-3196 was associated with lymph node metastasis and Tumor Node Metastasis (TNM) stage. The Kaplan-Meier curve analysis indicated that patients with low expression of microRNA-3196 had a poor prognosis, and the Cox regression analysis results showed microRNA-3196 expression was an independent prognostic factor of gastric cancer. Moreover, overexpression of microRNA-3196 inhibited cell proliferation, migration, and invasion, while knockdown of microRNA-3196 promoted these cellular behaviors in AGS and MKN45 cells. OTX1 may be a potential target gene regulated by microRNA-3196 in gastric cancer. Conclusions: These results suggested that microRNA-3196 might not only a tumor suppressor in gastric cancer cells by modulating OTX1 but also might be an independent prognostic biomarker and therapeutic target of gastric cancer.